Synthesis and Biological Evaluation of 3, 5‐Dimethoxystilbene Analogs. Issue 9 (8th September 2016) - Weng, Jian‐Quan; Ali, Abbas; Estep, Alden; Becnel, James; Meyer, Susan L. F.; Wedge, David E.; Jacob, Melissa; Rimando, Agnes M.
Abstract : In our continuing effort to discover natural product‐based pest management agents, derivatives of 3, 5‐dimethoxystilbene were synthesized yielding 27 new and six known compounds. Compounds11 and12 showed strong Aedes aegypti larvicidal activity ( LC 50 45.31 and 49.93 μm, respectively). Furthermore, 11 and12 exhibited high effectiveness against larvae of pesticide‐susceptible and pyrethroid‐resistant strains of Ae . aegypti ; activity against the adult mosquitoes was low. Compounds6f, 6g, and6i at either 83.3 or 166.7 μg/ml reduced the mobility of second‐stage juveniles (J2) of the root‐knot nematode ( Meloidogyne incognita ) that hatched from eggs immersed in the test compounds for 7 days. However, there was little or no effect on J2 placed directly into these compounds, and none of the analogs suppressed M . incognita egg hatch. The compounds were tested for inhibition of some agriculturally important fungi;6a, 7a, and7e demonstrated strong inhibition of Colletotrichum species. Activity of the stilbenes against some human pathogens was also explored;11, 12, and16 showed moderate inhibitory activity against Cryptococcus neoformans, Staphylococcus aureus, methicillin‐resistant S . aureus, and Mycobacterium intracellulare . Except for11 and12, which were active against mosquito larvae and some human pathogens, no single analog demonstrated activity in all the tests, indicating specific activities. Synthesis of the analogs and structure–activity relationships are discussed. Abstract :